Industry Change and Union Mergers in British Retail Finance - Morris, T; Storey, J; Wilkinson, A (2001)
This paper investigates the reasons for and implications of the recent merger between three of the largest unions in the retail finance sector, creating UNIFI. Recent union mergers have been explained by environmental changes adversely affecting membership and finances. These prompt leaders to consider merger as an appropriate organizational solution. Mergers are successfully concluded when leaders are able to overcome internal resistance and develop acceptable outcomes. We examine whether these factors are sufficient to explain how the merger between the national banking union and two large company-based staff unions was concluded, given longstanding institutional rivalry.